LONGITUDINAL AERODYNAMIC PARAMETERS ESTIMATION OF A SMALL UNMANNED AIRCRAFT VEHICLE USING SIMULATION DATA - Safi'i, Imam
In this study, estimation of longitudinal aerodynamic parameters of a small unmanned aircraft vehicle (UAV) is conducted using simulation data. As the first step, a dynamics model of the UAV is developed by using previously developed data. To generate flight test data, flight maneuver simulations are performed with certain input. The flight variables of the UAV are recorded and added with noise to simulate the characteristics of the sensors. Digital filter is used to suppress measurement noise in the measured data. Some flight variables which are not measured directly are reconstructed through numerical differentiation and flight path reconstruction (FPR) process. Estimation of longitudinal aerodynamic parameters is conducted using several estimators, i.e. ordinary least squares (OLS) method, output error method (OEM), and filter error method (FEM). The aerodynamic structure and parameters are adjusted to the aerodynamic model used to make the dynamic model of the UAV. Finally, validation and predictive ability test are conducted to the aerodynamic models.